Post occupancy evaluation for functional aspects with emphasis on emergency evacuation - Forest Jieprang (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2016)
Post occupancy evaluation is a tool to measure the qualities of an in-use building with the purpose of increasing the qualities of the building from the perspective which design process could overlook. There is a lot of aspects that has to be evaluated in the post occupancy evaluation, but the most frequently evaluated aspects are technical aspects, functional aspects, and behavioral aspects. This research emphasizes on the functional aspect to search for problems concerning evacuation circulation of Si Jalak Harupat Stadium by comparing observed object with the experience of users in how they recognize and aware of emergency evacuation elements. Users experience will be collected by using questionnaire and mental mapping. The respondents are Persib supporters who watch the matches at Si Jalak Harupat Stadium. Both of the tools will describe user perception and knowledge regarding evacuation elements legibility. This research will be concluded by describing just how far the evacuation elements of Si Jalak Harupat Stadium known by the users and find the solution to increase users awareness regarding evacuation elements inside the stadium.